Pembuatan Geopolimer Ringan Berbasis Fly Ash Batubara Dengan Penambahan Styrofoam - Nurwulandari Saputri; Amun Amri; Aman Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to make coal fly ash based light geopolymers with the addition of styrofoam as a lightweight aggregate. The light geopolymers was prepared by mixing the coal fly ash and high concentration of alkaline activator solution, with styrofoam. The mixture was then molded and formed to the geopolymers mortar and cured at temperature of 25℃ for 28 days. The results indicated that the addition of styrofoam decreased the compressive strength and density of geopolymer mortar. The highest compressive strength was obtained from sample with the addition of 1.5% -wt styrofoam and the size of 1 > x ≤ 5 mm styrofoam, which 8.8 MPa. The mechanical properties of geopolymer mortar were affected by the amount of styrofoam added and the size distribution of styrofoam in the geopolymer matrix. Keywords : alkali activators, geopolymer, styrofoam